Implementation of Character Education Based on Islamic Boarding Schools in Musical Arts Education - Desty Dwi Rochmania; Emy Yunita Rahma Pratiwi; Heru Wiyadi (Universitas Pendidikan Ganesha, 2022)
The existence of problems or a decrease in students' character in lectures is inversely proportional to their activities while at the cottage. The problems of students being in the field (campus), namely lack concern for the environment such as lack of discipline, being late for class, chatting during lectures, and low responsibility for college assignments. This study aims to apply Islamic boarding school-based character education in music education. This type of research is classroom action research. The subjects of this study amounted to 20 people. This writing uses the descriptive analysis method. Data collection techniques used are interviews, observations, and documentation. Data analysis with a qualitative descriptive approach uses descriptive techniques using three steps, namely data reduction, data presentation, and concluding. The implementation of pesantren-based character education in learning music initially received a poor response from the students. However, after walking, the students experienced changes in attitudes and behavior and began to know the importance of learning and studying. This paper concludes that applying Islamic boarding school-based character education in music education courses can instill character values ​​in students. These character values ​​include; independence/toughness, cooperation, honesty, discipline, and activity and diligence in learning.